PERLINDUNGAN KONSUMEN DALAM PERKEMBANGAN FINANCIAL TECHNOLOGY DI INDONESIA - Ulya, Widadatul (Perwira Journal of Economics & Business, 2022)
Financial Technology or commonly called Fintech makes it easier for people to buy and sell, one of which is buying and selling on e-commerce. Fintech provides various conveniences for creating accounts and transacting. The features provided is very varied, ranging from payment services, loans, installments, pay later (pay later). Fintech has contributed positively to the economic growth of 0.45% and gross domestic product (GDP) of more than Rp. 60 trillion, during the pandemic. These advantages and conveniences have an impact on consumer carelessness, so that many consumers are caught in the case. Illegal Fintech Lending and theft of personal data. Thus, it is very important to have legal protection for Fintech consumers. This study uses a normative juridical method, by collecting secondary data. Furthermore, the data were analyzed using a statutory approach and with a qualitative normative analysis method. The results of the study show that consumer protection for Financial Technology is carried out in a preventive and repressive manner. It is carried out preventively through laws and regulations and repressively carried out by the organizers and the OJK.